(3GdPNjQI aj eMGSf Cgd GdLRjQIs - (3Ydj Hf HSGe GdTfJQjfj GdCfOdSj, CHh GdMSf,J (B542 (3g` s
(3ChdgG (B:s
(3PcQ GdLGfH GdTQbj ef LRjQI GdCfOdS JSejJg ef fLe aj Cabg ef chGcH GdYUhQ s
(3BNQgG (B:s
(3HJQLeI GdhRjQ GdcGJH CHj HcQ Hf Pj GdhRGQJjf CHj GdMSjf EHf QMHe s
(3GdbFe GdKGdK ef fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B266 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B43s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B339 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B579 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B184 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B(4) s
Keywords: (3GdJGQjNs